Elaboracíon de los estudios de pre-factibilidad para la creación de una empresa de lavado de automóviles a domicilio con productos biodegradables en la ciudad Bogotá (2014)
Taking into account the relevance of the planning and control in the projects, the Project Book is developed, which aims to be a guide that must be taken into account at the time of preparation of the pre-feasibility studies, in this case relating it to the project: Creation of a home car wash company with biodegradable products in the city of Bogotá. For the development of this Management Plan, there are PMI and PMBOK guidelines provided by the Specialization in Development and Integral Project Management of the Julio Garavito School of Engineers.